2014
DOI: 10.1080/15374416.2013.865195
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Religiosity Buffers the Longitudinal Effects of Peer Victimization on Adolescent Depressive Symptoms

Abstract: Peer victimization is a common and potentially detrimental experience for many adolescents. However, not all youth who are exposed to peer victimization experience maladaptive outcomes, such as depression. Thus, greater attention to potential moderators of peer victimization is particularly important. The current study examined the potential moderating effect of intrinsic religiosity and religious attendance on the longitudinal association between physical and relational victimization and depressive symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Interestingly, higher serum brain-derived neurotrophic factor levels were found in MDD patients with higher intrinsic religiousness, and this may be one of the neurobiological explanations of positive effects of PRC in MDD and suicidal ideation [81]. We can argue that intrinsic religiousness and PRC enhance personal resilience at several levels, thus reducing the severity of depression and the emergence of suicidal ideation and behaviors [79,82]. On the other hand, NRC is associated with the extrinsic religiousness (i.e., the use of religion for a variety of personal needs such as security, status, or social support) and this is considered as a potential risk factor for MDD, lower self-control, and suicide [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, higher serum brain-derived neurotrophic factor levels were found in MDD patients with higher intrinsic religiousness, and this may be one of the neurobiological explanations of positive effects of PRC in MDD and suicidal ideation [81]. We can argue that intrinsic religiousness and PRC enhance personal resilience at several levels, thus reducing the severity of depression and the emergence of suicidal ideation and behaviors [79,82]. On the other hand, NRC is associated with the extrinsic religiousness (i.e., the use of religion for a variety of personal needs such as security, status, or social support) and this is considered as a potential risk factor for MDD, lower self-control, and suicide [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…Although interactions were only statistically significant about half of the time, they provide evidence for this protective effect of RS. In terms of buffering against risks, although findings are somewhat mixed, there is evidence that the more religious or spiritual teens are the less likely they are to experience negative outcomes (particularly substance use, externalizing, and internalizing) from daily stressors and adverse life events (e.g., Belgrave et al, 2010;Wills, Yaeger, & Sandy, 2003), parental substance use (e.g., Haber & Jacob, 2007;Yu & Stiffman, 2007), victimization by family, peers, or community members (e.g., Helms et al, 2015;Pearce, Jones, Schwab-stone, & Ruchkin, 2003;Phan & Kingree, 2001), exposure to political or community violence (e.g., Barber, 2001;Pearce et al, 2003;Shannon, Oakes, Scheers, Richardson, & Stills, 2013), and high sensation seeking or impulsivity (Laird, Marks, & Marrero, 2011;Salas-Wright, Vaughn, Maynard, Clark, & Snyder, 2017). Interestingly, negative religious coping worsens the negative impact of risk factors (Carpenter, Laney, & Mezulis, 2012;Terreri & Glenwick, 2013).…”
Section: (Q4) Are Relations Between Rs and Youth Outcomes Causal?mentioning
confidence: 99%
“…A previous study found that relational bullying (social exclusion and rumor spreading) had the strongest association with mental health problems, independent of verbal and physical bullying ( 49 ). Another study suggested that relational bullying may be especially detrimental to adolescent adjustment ( 50 ). This form of bullying generally causes a more adverse impact on adolescent self-esteem and social status than other forms of bullying ( 33 ).…”
Section: Discussionmentioning
confidence: 99%